Computer communication using serial interface c/w sampled data transfer / Mohd Fuad Junaidi - Junaidi, Mohd Fuad (1994)
Generally, a computer should be able to communicate with another nearby computer, either directly or through a modem that transmits over long distances through telephone lines. Such data transfer is normally done with the bits of the bytes transmitted serially over a transmission line. In this project, serial transmission scheme was used for the communications between the computers. Two types of serial transmission which are known as synchronous and asynchronous methods can be used to the system, thus some studies was done to select the best method. Considering some factors, asynchronous transmission method with a low bit rate was applied to the system. The software which is the important part of the system was developed to enable the computers to communicate with each other. The progarm was based on UART which is a built-in device in the computer.